Effect of Ore Type and Size Distribution on the Granulating Characteristics of Iron Ore - R Muddle; J Manuel (The Australasian Institute of Mining and Metallurgy, 2005)
The demand for iron ore has increased significantly in recent years, with new iron ore sources being mined to meet this demand. As the composition of sinter blends changes with the availability and cost of iron ore, so too does interest in the impact of new ore types on granulation and ultimately productivity. This paper describes a study into granulating characteristics of seven iron ore types, including various hematite and goethite ores. The effect of ore type on feed moisture requirements, green bed permeability, green bed strength and granule size distribution was examined for single ore blends containing coke, flux and returns. The ore size distribution was varied in these blends and its effect on granulating characteristics examined. It was found that the optimum moisture requirement of the ore was more dependent on ore type than ore size distribution, but ore size distribution (and specifically intermediate particle loading) had a greater effect on green bed permeability. The saturation moisture value for an ore was found useful in predicting both optimum granulation moisture and green bed permeability.